2016
DOI: 10.1016/j.spl.2016.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Double asymptotics for the chi-square statistic

Abstract: Consider distributional limit of the Pearson chi-square statistic when the number of classes mn increases with the sample size n and n/mn→λ. Under mild moment conditions, the limit is Gaussian for λ = ∞, Poisson for finite λ > 0, and degenerate for λ = 0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…The asymptotic behavior of Pearson's chi-squared statistic has been well studied in the literature (Read and Cressie, 2012, for a review). In the high-dimensional case where the dimension (the number of bins) increases with the sample size, Rempała and Wesołowski (2016) investigate both the Poisson and Gaussian approximations for χ 2 n . Specifically, when π 0 is uniformly distributed, they show that χ 2 n is asymptotically Poisson when n/ √ d → c ∈ (0, ∞) and asymptotically Gaussian when n/ √ d → ∞.…”
Section: High-dimensional Asymptoticsmentioning
confidence: 99%
“…The asymptotic behavior of Pearson's chi-squared statistic has been well studied in the literature (Read and Cressie, 2012, for a review). In the high-dimensional case where the dimension (the number of bins) increases with the sample size, Rempała and Wesołowski (2016) investigate both the Poisson and Gaussian approximations for χ 2 n . Specifically, when π 0 is uniformly distributed, they show that χ 2 n is asymptotically Poisson when n/ √ d → c ∈ (0, ∞) and asymptotically Gaussian when n/ √ d → ∞.…”
Section: High-dimensional Asymptoticsmentioning
confidence: 99%
“…By using estimators a and b, the value of each parameter can be seen on table 2 below: --The use of mathematical model to predict the condition of the unit in the future certainly must involve suitability evaluation of the model (goodness of fit). Statistical method that often used to evaluate suitability of the model is Pearson's Chi-squared Test [7]. This method compares the amount of actual failure at a predetermined time interval, in this research is 6 months, with the expected amount of failure obtained from mathematical model that has been made.…”
Section: Unitmentioning
confidence: 99%
“…In this paper, we are interested in the goodness-of-fit test when both n and k go to infinity, that is, we allow that k = k n changes with n and k n can be even much larger than n. We note that asymptotic normality of Pearson's chi-squared test statistics has been obtained by Tumanyan [18] and Holst [7] when n/k n → a ∈ (0, ∞) and some restrictive conditions are held. A recent work by Rempa la and Weso lowski [17] extended this scope by imposing conditions on the following decomposition of Pearson By assuming that S n2 is negligible, Rempa la and Weso lowski [17] showed that X 2 n is asymptotically normal if n 2 /k n → ∞ as n → ∞. The conditions imposed in Rempa la and Weso lowski [17] will be discussed further in Section 2.…”
mentioning
confidence: 99%
“…A recent work by Rempa la and Weso lowski [17] extended this scope by imposing conditions on the following decomposition of Pearson By assuming that S n2 is negligible, Rempa la and Weso lowski [17] showed that X 2 n is asymptotically normal if n 2 /k n → ∞ as n → ∞. The conditions imposed in Rempa la and Weso lowski [17] will be discussed further in Section 2. Since the negligibility condition is trivially true for equiprobable cells, that is, p 1 = • • • = p kn , X 2 n has a normal limit, and furthermore, Rempa la and Weso lowski [17] showed in this case that X 2 n , after properly normalized, converges in distribution to a Poisson distribution if n 2 /k n → λ ∈ (0, ∞).…”
mentioning
confidence: 99%
See 1 more Smart Citation